2023
DOI: 10.3390/w15081518
|View full text |Cite
|
Sign up to set email alerts
|

Rainwater Harvesting and Treatment: State of the Art and Perspectives

Abstract: Rainwater harvesting is an ancient practice currently used for flood and drought risk mitigation. It is a well-known solution with different levels of advanced technology associated with it. This study is aimed at reviewing the state of the art with regards to rainwater harvesting, treatment, and management. It focuses on the environmental and social benefits of rainwater harvesting and links them to the Sustainable Development Goals. The review identifies characteristics of laws and regulations that encourage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 137 publications
0
25
0
Order By: Relevance
“…It first passes through filter 1 with a 20 μm pore-size polypropylene cartridge (3), then through filter 2 with a 5 μm pore-size polypropylene cartridge (4) and finally through filter 3 with an activated carbon cartridge (5). Microbial contaminants, especially coliform bacteria originating from avian faecal droppings accumulated on the roofs, are removed with a UV disinfection lamp (Eko Technika (Gliwice, Poland) TMA D6, 2.3 m 3 /h) (6). Because the effectiveness of the lamp is strongly contingent on water clarity, it is located at the end of the treatment train, downstream of the three filters.…”
Section: Characteristics Of the Rainwater Treatment Systemmentioning
confidence: 99%
See 3 more Smart Citations
“…It first passes through filter 1 with a 20 μm pore-size polypropylene cartridge (3), then through filter 2 with a 5 μm pore-size polypropylene cartridge (4) and finally through filter 3 with an activated carbon cartridge (5). Microbial contaminants, especially coliform bacteria originating from avian faecal droppings accumulated on the roofs, are removed with a UV disinfection lamp (Eko Technika (Gliwice, Poland) TMA D6, 2.3 m 3 /h) (6). Because the effectiveness of the lamp is strongly contingent on water clarity, it is located at the end of the treatment train, downstream of the three filters.…”
Section: Characteristics Of the Rainwater Treatment Systemmentioning
confidence: 99%
“…Recently, more and more research indicates that the harvesting and utilisation of rainwater can help to surmount the problems connected with water deficits caused by climate change in various regions of the world [4,5]. Raimondi et al [6] have reported that the number of publications recorded yearly in the Scopus database containing the keyword "rainwater harvesting" increased from zero in 1985 to over 400 in 2021. According to the UN, climate change is the greatest threat to social and economic development.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rainwater harvesting is an ancient practice that was used to combat the risk of floods and droughts; it is currently more important because it helps supply water needs in areas where there is a water shortage [1].…”
Section: Introductionmentioning
confidence: 99%